Development and Application of Functionally Gradient Materials - Tao Jun (2012 International Conference on Industrial Control and Electronics Engineering, 2012)
The paper introduces the conception, the origin, the development and the current situation of functionally gradient materials (FGM). The characteristics and advantages of FGM are shown completely by comparing it with other materials. The main research field of FGM is expatiated from three aspects of design, preparation and evaluation. The application trend of FGM is prospected finally in the paper.